Special educational needs a guide for inclusive practice - Peer, Lindsay; Reid, Gavin 1950- (SAGE, 2016)
Covering contemporary policy issues, perspectives from practice and a range of common syndromes and barriers Special Educational Needs presents a wealth of information and guidance for students and professionals on how to achieve effective, inclusive practice.